Gilligan's island. The complete first season - Backus, Jim.; Schafer, Natalie, 1900-1991.; Denver, Bob.; Tina Louise, 1934-; Hale, Alan, 1918-1990.; Warner Home Video (Firm); Warner Bros. ([United States] : Warner Home Video, 2011)
After a three-hour pleasure cruise, the SS Minnow is washed ashore on an uncharted South Pacific island, leaving behind what would become TV's most famous castaways. Episodes include the: Two on a Raft; Home Sweet Hut; Voodoo Something To Me; Goodnight Sweet Skipper; Wrongway Feldman; President Gilligan; and many more. This title has been repackaged.
Title from the Web.
Originally released as a motion picture in 1972.
Release date: Apr. 3, 2012.
Bob Denver, Tina Louise, Alan Hale, Jr., Jim Backus, Natalie Schafer, Dawn Wells, Russell Johnson.
Rating: Not rated.
DVD.
Keywords: Ship captains -- Drama; Castaways -- Drama; Islands of the Pacific -- Drama; Television comedies; Video recordings for the hearing impaired